Forecasting Movie Box Office Profitability - Galvão, Marta (2018)
Galvão, M., & Henriques, R. (2018). Forecasting Movie Box Office Profitability. Journal of Information Systems Engineering & Management, 3(3), 1-9. [22]. DOI: 10.20897/jisem/2658